Nurses and Physicians\' Viewpoint toward Interprofessional Collaboration - M Jasemi; A Rahmani; N Aghakhani; FS Hosseini; S Eghtedar (Iran University of Medical Sciences, 2013)
Background and Aim : Collaboration between nurses and physicians is essential for providing primary care and it is key factor for facilitating empowerment and rehabilitation of patients. This study by determining viewpoints of nurses and physicians toward professional collaboration tries to determine the existing conditions and to fasilate collaboration between nurses and physicians.   Material &Methods: This cross-sectional study assessed the viewpoints of 134 nurses and 66 physicians regarding interproffeshional collaboration in teaching hospitals of Tabriz-Iran. The data were collected by Jefferson questionnaire. Its reliability was 0.86 by using test- retest and its validity was received by content validity. Data was analyzed by SPSS-PC(v.13) software and using of pearson, One-way ANOVA and independent T test.   Results: The results showed that the physicians' attitudes toward profesional collaboration was not so good in physician's dominance and nurses' autonomy subscales. There were significant differences between the nurses' and physicians' viewpoints in the subscales of: physician's dominance(p<0.001), nurses' autonomy (p<0.001), teamwork (p=0.003) and caring as opposed to curing (p<0.001).Assessing relationship between demographic variables of nurses and physicians and their viewpoint toward interprofessional collaboration showed direct relation between physicians' viewpoint and their experience(p=0.008,r-0.42) but, this relationship was reversed in nurses and their viewpoint had been worse with increasing experience(p=0.03,r- -0.38). Nurses and physicians' viewpoint toward interprofessional collaboration in I.C.U and C.C.U wards were better than general wards.   Conclusion: Regarding the undesirable attitude of physicians in the physicians' dominance and nurses' autonomy subscales, providing training programs for nursing and medical students about professional roles with emphasis on professional communication skills during their educational courses is recommended.   Received: 7 Apr 2013   Accepted: 26 Jun 2013